Development and Testing of Rescue Destruction Charges for the Demolition of Statically Unstable Buildings - Lichorobiec, Stanislav; Figuli, Lucia (Communications - Scientific letters of the University of Zilina, 2018)
Due to the industrial accidents (the effects of explosion of improvised explosive devices or gas) or other unexpected events, heavily damaged buildings represent threat to environment. Generally, their damage is so serious that their reconstruction is not considered and the only solution is a demolition. Advantageously emergency shaped explosive charges can be used in these risk situations of buildings that are beyond repair. With such shaped charges is possible to execute a fast and effective implosion of an unstable building without the posing any threathening effects on surrounding, mainly in urban areas. This papers is focused on the design and development of mentioned shaped explosive charges, their testing in the field test and practical applications.